International progress in precision engineering : proceedings of the 7th International Precision Engineering Seminar, Kobe, Japan, May 1993 - Ikawa, N. (Naoya) (Butterworth-Heinemann, 1993)
International Progress in Precision Engineering documents the proceedings of the 7th International Precision Engineering Seminar held in Kobe, Japan, May 1993. The seminar brought together the world's leading precision engineering practitioners from areas of application as diverse as sensors, actuators, scanning tip microscopy, micro and nano machining (including bio-machining), ultra precision measuring machines, machine tools, and large optics for space technology. The seminar included 10 oral sessions that dealt with the following topics: (I) Metrology - The Science Base For Precision Engin.